2022
DOI: 10.3390/plants11101347
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Somatic Embryogenesis in Tamarillo (Solanum betaceum Cav.) Involves Increases in the Endogenous Auxin Indole-3-Acetic Acid

Abstract: Somatic embryogenesis (SE) is a complex biological process regulated by several factors, such as the action of plant growth regulators, namely auxins, of which the most physiologically relevant is indole-3-acetic acid (IAA). In tamarillo, an optimized system for induction of SE creates, after an induction process, embryogenic (EC) and non-embryogenic callus (NEC). In this work the endogenous levels of auxin along the induction phase and in the calli samples were investigated using chemical quantifications by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Similarly, callus cultures of other in vitro recalcitrant barley cultivars (“Haruna Nijo” and “Morex”) accumulated IAA at a level different from the GP culture (Hisano et al 2016 ). Although the links between auxin content in explants/callus and the plant regeneration potential were also reported in other plant species (Nic-Can and Loyola-Vargas 2016 ), in vitro responding genotypes indicated both higher and lower accumulation of IAA than those in vitro recalcitrant (Żur et al 2015 ; Hisano et al 2016 ; Grzyb et al 2017 ; Caeiro et al 2022 ).…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, callus cultures of other in vitro recalcitrant barley cultivars (“Haruna Nijo” and “Morex”) accumulated IAA at a level different from the GP culture (Hisano et al 2016 ). Although the links between auxin content in explants/callus and the plant regeneration potential were also reported in other plant species (Nic-Can and Loyola-Vargas 2016 ), in vitro responding genotypes indicated both higher and lower accumulation of IAA than those in vitro recalcitrant (Żur et al 2015 ; Hisano et al 2016 ; Grzyb et al 2017 ; Caeiro et al 2022 ).…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, the expression of MoIAA13 (lamu_GLEAN_10011219) increased with increasing treatment time ( Figure 7 ). IAA11 and IAA14 gene expression exhibits a general downward trend throughout the embryogenic callus induction process in Tamarillo, while IAA17 expression appears greater than that in the initial explant [ 41 ]. Other research has revealed that shoot regeneration ability was hampered by increased IAA12 expression [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, IAA was found to be highly accumulated in EC ( Supplementary Table 3 ), which may be attributed to the higher expression level of one YUC gene (Lk07754) and one TAA1 gene (Lk22753) in EC. IAA participation in maintenance of multiplying cells has been demonstrated in SE of rubber tree ( Hevea brasiliensis ), and the higher accumulation of IAA in EC compared to NEC have been reported in Douglas-fir ( Pseudotsuga menziesii ) and Tamarillo ( Solanum betaceum ) ( Gautier et al., 2019 ; Caeiro et al., 2022 ). Additionally, it has been reported that the increase in endogenous auxin biosynthesis play a role in determining developmental cell fate and in activating the proliferative activity of proembryo cells ( Pérez-Pérez et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%